Iron supply from the Oregon margin to the ocean dominated by hypoxia-dependent particles - Alexis E. Floback; Anh Le-Duy Pham; Pierre Damien; Catherine E. Odendahl; Jennifer Weiske; Katherine E. Thomas; Justin Gaffney; Seth G. John; Daniele Bianchi; James W. Moffett (Proceedings of the National Academy of Sciences, 2026)
Continental margins are sources of iron (Fe), a critical oceanic micronutrient limiting productivity over nearly a third of the ocean. Paradoxically, they are also sinks of Fe and other particle-reactive elements that are sequestered in margin sediments. When dissolved Fe is released from reducing sediments, most is retained on the shelf by oxidative scavenging (“Fe trapping”), severely constraining cross-shelf export of dissolved Fe. However, observations from the Oregon shelf in 2021 show that cross-shelf export is overwhelmingly dominated by particulate Fe, forming persistent, particle-rich plumes that extend well beyond the shelf-slope break. Particles accumulate in a 30 m thick benthic nepheloid layer within hypoxic zones overlying the continental shelf sediments, previously shown to be a strong source of reduced iron. Surprisingly, resuspended particulate Fe includes both nonlithogenic and lithogenic components, suggesting that hypoxia influences particle buoyancy and resuspension, consistent with recent advances in organic geochemistry. A physical-biogeochemical model that incorporates oxygen-dependent particle sources and realistic settling velocities reproduces the distribution of particle-rich plumes, highlighting the dynamic physical processes driving cross-shelf export of particulate Fe. We propose that increases in particle buoyancy is a previously unrecognized mechanism linking hypoxia and Fe mobilization acting in tandem with well-established redox processes. Particles settle on the continental slope and supply large Fe plumes extending westward from the slope from 200 m to 2,000 m. Simulations with an inverse model show that these plumes outcrop in Fe-limited high nutrient low chlorophyll regions. Thus, local and regional hypoxia on the margins could have basin-scale biogeochemical impacts.